Pengaruh Dukungan Sosial Keluarga dan Gaya Komunikasi Perawat terhadap Tingkat Kecemasan Pasien Pra-Operasi - Solehudin, Solehudin; Syabanasyah, Inas (Barongko: Jurnal Ilmu Kesehatan, 2025)
Preoperative anxiety is a common psychological response experienced by patients undergoing surgical procedures, and this condition can affect physiological stability as well as the overall recovery process. Family social support and nurses’ communication style are two critical factors that play a significant role in reducing such anxiety. This study aims to analyze the influence of family social support and nurses’ communication style on the level of preoperative anxiety among patients. The research employed a quantitative approach using a correlational analytic method and logistic regression analysis. The sample consisted of 74 respondents undergoing elective surgery, selected through incidental sampling. The findings revealed that family social support had a significant effect on preoperative anxiety (p = 0,004; Estimate = 3.75), and nurses’ communication style also demonstrated a significant influence (p = 0.015; Estimate = 3.21). These results indicate that better family support and more effective communication styles used by nurses are associated with lower levels of preoperative anxiety. This study underscores the importance of family involvement and nurses’ therapeutic communication skills as integral components of preoperative nursing interventions. The implementation of empathetic, clear, and informative communication strategies, along with structured family education, is recommended to enhance patients’ psychological comfort.